Neuronally produced versican V2 renders C‐fiber nociceptors IB4‐positive. (27th April 2015) - Bogen, Oliver; Bender, Olaf; Löwe, Jana; Blenau, Wolfgang; Thevis, Beatrice; Schröder, Wolfgang; Margolis, Richard U.; Levine, Jon D.; Hucho, Ferdinand
Abstract A subpopulation of nociceptors, the glial cell line‐derived neurotrophic factor (GDNF)‐dependent, non‐peptidergic C‐fibers, expresses a cell‐surface glycoconjugate that can be selectively labeled with isolectin B4 (IB4), a homotetrameric plant lectin from Griffonia simplicifolia. We show that versican is an IB4‐binding molecule in rat dorsal root ganglion neurons. Using reverse transcriptase polymerase chain reaction (RT‐PCR), in situ hybridization and immunofluorescence experiments on rat lumbar dorsal root ganglion, we provide the first demonstration that versican is produced by neurons. In addition, by probing Western blots with splice variant‐specific antibodies we show that the IB4‐binding versican contains only the glycosaminoglycan alpha domain. Our data support V2 as the versican isoform that renders this subpopulation of nociceptors IB4‐positive (+). A subset of nociceptors, the GDNF‐dependent non‐peptidergic C‐fibers can be characterized by its reactivity for isolectin B4 (IB4), a plant lectin from Griffonia simplicifolia. We have previously demonstrated that versican V2 binds IB4 in a Ca2 + ‐dependent manner. However, given that versican is thought to be the product of glial cells, it was questionable whether versican V2 can be accountable for the IB4‐reactivity of this subset of nociceptors. The results presented here prove – for the first time – a neuronal origin of versican and suggest that versican V2 is the molecule that renders GDNF‐dependent non‐peptidergic C‐fibers IB4‐positive.